PEMBUATAN TEMPAT SAMPAH BERBAHAN DASAR BOTOL BEKAS SEBAGAI UPAYA PELESTARIAN LINGKUNGAN SEKOLAH BEBAS SAMPAH PLASTIK DI UPTD SDI WAEWARU - Maria Goreti Kui; Ngura Mahendra Dinatha; Afrianus Gelu (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
One alternative that can be done to minimize the increase in plastic waste is to recycle the waste into valuable goods or objects such as trash cans. By utilizing waste from plastic bottles into trash cans, little by little we can reduce the amount of waste, especially plastic bottles, and improve the quality of cleanliness of the surrounding environment. The type of method used in this activity is direct observation which is combined in the form of a system of action or service. This activity was carried out at UPTD SD Inpres Wewaru, Aimere sub-district, starting on October 15 and ending on November 5 2023. This form of service consists of several stages including the planning stage, preparation stage, implementation stage and evaluation stage. The results of this service show that not all waste has a bad impact on society, there is some waste that has a positive impact. This happens if waste is used for things that are beneficial to society.